THE EFFECT OF GENIALLY ON STUDENTS’ READING SKILL - Tharissa Rahmanda Syafitri; Wahyu Diny Sujannah (PROJECT (Professional Journal of English Education), 2024)
This pre-experimental study aimed to know the effect of Genially on students’ reading skill. This study only focus on students’ reading skills improvement. The participants were 34 tenth-grade Academic Hospitality students in one of the State Vocational High Schools in Malang. The data had been using one group to be tested. This research used pre-test and post-test as the instruments and the participants were given treatment in the form of using Genially as the teaching tool in learning reading. The data were tested by using normality on SPSS 26 version. The findings showed that Genially was effective in improving students’ skills in reading recount texts because they were interested to the interactive design and willing to read the texts. Thus, it is recommended that English teachers use Genially to teach reading inside and outside classroom through interactive presentation and gamification as teaching media to engage students’ motivation. Furthermore, it is also suggested that future researchers investigate the students’ perspective on using Genially to improve their reading skill.